The Impact of PREP Training on Marital Conflicts Reduction: A Randomized Controlled Trial With Iranian Distressed Couples. Issue 1 (2nd January 2017) - Fallahchai, Reza; Fallahi, Maryam; Ritchie, Lane L.
ABSTRACT: The purpose of this study was to examine the efficacy of the Prevention and Relationship Education Program (PREP) training on marital conflict and marital satisfaction among a sample of distressed couples in Iran. The research procedure was experimental with a pretest, posttest, and follow-up design, including a control group. The sample included 76 volunteer couples among a sample of distressed couples who were randomly selected and assigned to the experimental or control group. They completed demographic questions, the Marital Conflicts questionnaire, and a revised Marital Satisfaction Inventory in pretest, posttest and at the 1-year follow-up. Results showed that PREP training effectively led to decreased marital conflict and improvement of marital satisfaction of couples at posttest and at the 1-year follow-up. The result of covariance analysis showed significant differences between the experimental and the control groups' marital conflict and marital satisfaction at posttest and at the 1-year follow-up.